N-термальний натрійуретичний мозковий пептид, параметри інсулінової резистентності у хворих на цукровий діабет 2-го типу та ішемічну хворобу серця - Сергієнко, В. О.; Суслик, Г. І.; Урбанович, А. М.; Сергієнко, О. О. (Clinical Endocrinology and Endocrine Surgery, 2012)
The aim was to study the concentration of the fragment of brain natriuretic peptide (NT-proBNP), parameters of insulin resistance (IR) in patients with type 2 diabetes and CAD. A total of 65 patients with type 2 diabetes mellitus and CHD, 22 patients with type 2 diabetes mellitus without verified coronary artery disease, 30 patients with coronary artery disease and a physiological glucose tolerance test. Study groups were matched for age and duration of illness. Levels of immunoreactive insulin, NT-proBNP, indices of insulin resistance in the blood of patients were observed. It was established, that patients with type 2 diabetes mellitus with CHD experienced higher circulating levels of insulin in the blood, revealed timber Most high NT-proBNP concentration in the blood, which may be an indirect indicator of the prevalence of myocardial ischemia and a marker of long-term prognosis of cardiac accidents. Between indices of insulin resistance and the concentration of NT-proBNP exists medium strength positive correlation.